davidgoes4wce
Well-Known Member
Re: HSC 2016 3U Marathon
makes it :
![](https://latex.codecogs.com/png.latex?\bg_white (x-2)^2=4a [(2x-7)+1] )
![](https://latex.codecogs.com/png.latex?\bg_white x^2-4x+4=4a(2x-6) )
![](https://latex.codecogs.com/png.latex?\bg_white x^2-x(4-8a)+(4-24a)=0 )
![](https://latex.codecogs.com/png.latex?\bg_white \triangle =b^2-4ac=0 )
![](https://latex.codecogs.com/png.latex?\bg_white (4-8a)^2-4(4-24a)=0 )
![](https://latex.codecogs.com/png.latex?\bg_white 16-64a+64a^2-16+96a=0 )
![](https://latex.codecogs.com/png.latex?\bg_white 64a^2+32a=0 \implies 32a(2a+1)=0 )
![](https://latex.codecogs.com/png.latex?\bg_white a=\frac{-1}{2} )
a cannot be 0 in this case because it must be a quadratic form.
So you say let y=2x-7 (which I didn't get at the time)The parabola takes the form (x-2)^2=4a(y+1)
A wolfram alpha approach: Sub y=2x-7 in and simplify the expression
Take the quadratic discriminant, set it equal to 0 and take your value for a
makes it :
a cannot be 0 in this case because it must be a quadratic form.